Morphologic changes and the expression of alpha-melanocyte stimulating hormone and melanocortin-1 receptor in melasma lesions: A comparative study - Miot, Luciane D. [UNESP]; Miot, Hélio Amante [UNESP]; Polettini, Jossimara [UNESP]; Silva, Marcia Guimarães da [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Wolters Kluwer, 2010)
Melasma is a common acquired symmetrical hypermelanosis characterized by irregular light- to dark-brown macules on sun-exposed skin areas. The literature shows few studies on its physiopathogeny. However, changes in α-melanocyte stimulating hormone (α-MSH) secretion and melanocortin-1 receptor (MC1-R) expression may play a role to trigger this condition. Biopsies were taken from both melasma skin and adjacent perilesional normal skin of 44 patients. The biopsies were submitted for hematoxylin and eosin and Fontana-Masson staining and immunohistochemistry with Melan-A, α-MSH, and MC1-R, and processed for transmission electron microscopy. In some cases, they were submitted to MC1-R gene expression analysis by real-time polymerase chain reaction. Increased lymphohistiocytic infiltrate and solar elastosis, higher epidermal melanin were observed in melasma skin. Electron microscopy revealed a greater number of mature melanosomes in keratinocytes and melanocytes, and more prominent cytoplasmic organelles in melasma skin. There was no difference in melanocyte number between areas. However, melanocytes were larger and more dendritic in melasma skin. Immunohistochemistry with α-MSH and MC1-R showed significant labeling in melasmic epidermis but MC1-R messenger ribonucleic acid (RNAm) did not show significant quantitative difference between melasma and normal skin. © 2010 by Lippincott Williams & Wilkins.
Keywords: alpha-MSH; immunohistochemistry; melanosis; polymerase chain reaction receptor; type 1 melanocortin; alpha intermedin; eosin; hematoxylin; melan A; melanin; melanocortin 1 receptor; messenger RNA; cell organelle; chloasma; clinical article; comparative study; controlled study; elastosis; gene expression; human; keratinocyte; lymphocytic infiltration; melanocyte; melanosome; morphology; priority journal; protein expression; quantitative analysis; real time polymerase chain reaction; skin biopsy; transmission electron microscopy; Female; Gene Expression; Humans; Image Processing, Computer-Assisted; Immunohistochemistry; Melanosis; Microscopy, Electron, Transmission; Receptor, Melanocortin, Type 1; Reverse Transcriptase Polymerase Chain Reaction